THE POLICY OF JOINT DEFENSE REGIONAL COMMAND I OF THE INDONESIAN MILITARY (KOGABWILHAN I TNI) IN SUPPORTING STATE DEFENSE - Yudhi Chandra Jaya; Guntur Eko Saputro; Cakrawati Sudjoko (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
Joint Defense Regional Command I (Kogabwilhan I) is the Operation Main Command (Kotamaops) of the Indonesian National Armed Forces (TNI or Tentara Nasional Indonesia) which is directly under the Commander of the Indonesian National Armed Forces. Kogabwilhan I’s task is to act as an initial follower and restorer in the event of a conflict in its territory, both for War Military Operations (WMO) and Military Operations Other Than War (MOOTW) as well as a deterrent in the event of a threat. The current phenomenon is that the organizational readiness of units in the Natuna area is not yet ideal, the readiness of human resources, especially the Indonesian National Armed Forces units in the Natuna area, is still limited, and the support for facilities and infrastructure of the Indonesian National Armed Forces units in the Natuna area is not adequate, and the implementation of operational activities in the Indonesian National Armed Forces units in the Natuna area. Natuna is not optimal. The purpose of this study is to provide government input on the implementation of Joint Defense Regional Command I (Kogabwilhan I) policies in supporting the national defense. This study uses a qualitative method which is an understanding of social phenomena from several participant perspectives. The results achieved are by the theory of Policy Implementation related to Resources, Communication, Disposition, and Bureaucratic Structure, a strategy is needed to revamp the bureaucratic structure and recalculate budget resources.